2016
DOI: 10.1016/j.jbi.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Current applications and future directions for the CDISC Operational Data Model standard: A methodological review

Abstract: Introduction In order to further advance research and development on the Clinical Data Interchange Standards Consortium (CDISC) Operational Data Model (ODM) standard, the existing research must be well understood. This paper presents a methodological review of the ODM literature. Specifically, it develops a classification schema to categorize the ODM literature according to how the standard has been applied within the clinical research data lifecycle. This paper suggests areas for future research and developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…The introduction of standardized disease severity scores will facilitate headto-head comparisons and the 'meta-analyzability' of clinical trials and observational studies. Full compliance of the ViVI Disease Severity Score mobile application with Clinical Data Interchange Standards Consortium (CDISC) standards further expands data interoperability and compliance with reporting formats to regulatory agencies [145][146][147][148][149][150].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of standardized disease severity scores will facilitate headto-head comparisons and the 'meta-analyzability' of clinical trials and observational studies. Full compliance of the ViVI Disease Severity Score mobile application with Clinical Data Interchange Standards Consortium (CDISC) standards further expands data interoperability and compliance with reporting formats to regulatory agencies [145][146][147][148][149][150].…”
Section: Discussionmentioning
confidence: 99%
“…The system includes forms from clinical and research systems and supports multi-lingual data files. A later examination of the ODM model has found that it is being used as a metadata standard for many use cases including Electronic Data Capture and Electronic Medical Records, data collection, data tabulation and analysis, and data archival [9]. Systems needing more features than the ODM model can be developed keeping many of the fundamental metadata design principles of multi-lingual and flexible communication in mind.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 ODM's hierarchical metadata structure has been used to generate data collection forms, decision support systems, and other applications. 12 ODM provides an extension mechanism to augment the model as needed to support specific interchange scenarios and alternative use cases. Define-XML, one such ODM extension, provides the metadata to describe tabular datasets and plays a key role in establishing traceability in regulatory submission datasets.…”
Section: Trace-xml Development and Evaluationmentioning
confidence: 99%
“…Define-XML, one such ODM extension, provides the metadata to describe tabular datasets and plays a key role in establishing traceability in regulatory submission datasets. 12,22 The FDA's March 2017 Study Data Technical Conformance Guide states that the Define-XML file "describes the metadata of the submitted electronic datasets and is considered arguably the most important part of the electronic dataset submission for regulatory review." 23…”
Section: Trace-xml Development and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation